Karakteristik Kimia, Sifat Fungsional, dan Prediksi Indeks Glikemik Tepung Komposit Berbasis Hanjeli (Coix lacryma-Jobi) Termodifikasi - Adelina, Nadya Mara; Aziz, Lukman; Fauziyah, A’immatul; Mevera, Khezia; Salmatyanti, Nesia Odnikana (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
In 2021, Indonesia ranked 5th globally for the highest number of diabetes cases, primarily due to excessive consumption of high-glycemic index foods. The glycemic index is influenced by fiber, minerals, bioactive compounds, and starch modification. This study aims to determine the optimal formulation of Heat Moisture Treatment (HMT) modified hanjeli flour, dragon fruit peel flour, and cashew nut flour to obtain composite flour with the lowest predicted glycemic index. The physical, functional, and chemical properties of the flour were also analyzed. A Completely Randomized Design (CRD) with one factor and five treatments was used. Composite flour was prepared by mixing dried ingredients using a food dehydrator. Results showed that sample F5 (45% dragon fruit peel flour) had the highest Water Holding Capacity (WHC) and Oil Holding Capacity (OHC). Fiber content, ash content, total phenolics, and resistant starch increased with the higher ratio of dragon fruit peel flour, whereas rapid digestible starch (RDS) and slow digestible starch (SDS) decreased as the proportion of modified hanjeli flour decreased. Sample F4 (50% modified hanjeli flour, 35% dragon fruit peel flour, and 15% cashew nut flour) had the lowest predicted glycemic index (40.53), making it a promising ingredient for low-glycemic index foods.Keywords – Bioactive Compounds, Diabetes, Fiber Content, Heat Moisture Treatment, Modified Starch.